The PISA Phenomenon: The Many Faces of International Student Assessment - Želvys, Rimantas (Acta Paedagogica Vilnensia, 2016)
The aim of this article is to explore the phenomenon of PISA – the Programme for International Student Assessment. The PISA study is a unique initiative in the contemporary educational world. Initiated in 2000 by OECD, currently it includes 65 countries and territories from all over the world. We decided to identify the multiple aspects, or, speaking metaphorically, the many faces of PISA, which carry different messages and are subject to different value judgements by various interest groups. In our publication, we discuss ten different aspects of PISA. PISA can be perceived as a symbol of globalisation, as a manifestation of neoliberal ideology in education, as a methodological controversy, as a research database, a benchmark, a league table, as promotion, as punishment, as business, and, finally, as policymaking. We conclude that the key actors of an educational domain should use various aspects of PISA survey in a more skillfull and selective way for achieving their goals and securing their interests.
Keywords: Programme for International Student Assessment (PISA); globalisation; neoliberal ideology; benchmarking; league table; policymaking